1975
DOI: 10.2135/cropsci1975.0011183x001500030039x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Beans to Shading1

Abstract: Two dry bean (Phaseolus vulgaris L.) cultivars were grown in controlled‐environment chambers under standard light [390 μ Einsteins m‐2 sec‐1 (400 to 700 nm) = approx. 22,000 lux] and shaded light [55 μ Einsteins m‐2 sec‐1 (400 to 700 nm) = approx. 3,200 lux] intensities. Experimental observations included measurement of gas exchange and photosynthetic and respiratory enzyme activity along with examination of plant morphology, leaf anatomy, and chloroplast ultrastructure.Shading reduced leaf number, area, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…Islam (1995) in mungbean and Crookston et al (1975) in dry bean also found decreased leaf number under shade condition. Similar result of decrease in leaf number due to shading was found in all legumes by Chiangmai et al (2013).…”
Section: Number Of Leaves Per Plantmentioning
confidence: 90%
See 1 more Smart Citation
“…Islam (1995) in mungbean and Crookston et al (1975) in dry bean also found decreased leaf number under shade condition. Similar result of decrease in leaf number due to shading was found in all legumes by Chiangmai et al (2013).…”
Section: Number Of Leaves Per Plantmentioning
confidence: 90%
“…Crookston et al (1975) reported that shading reduced leaf thickness of bean. Similar result of shading induced reduced thickness was found in all legumes by Chiangmai et al (2013) and Araki et al (2014).…”
Section: Thickness Of Palisade and Spongy Layermentioning
confidence: 99%
“…While studying beans (Phaseolus vulgaris L.), Crookston et al (1975) found that shading decreased the thickness of leaves as well as the photosynthetic activity per unit leaf area. This was ascribed to the sharp increase in mesophyll resistance, which they linked to the decreased enzymatic activity and alterations in leaf anatomy and chloroplast ultrastructure also found.…”
Section: Leaf Area:mass Ratiomentioning
confidence: 99%
“…This was due to the limitation of P N by low photosynthetic photon flux density. The mesophyll resistance, which is usually regarded as the sum of biophysical and biochemical resistances to CO 2 movement between the mesophyll cell wall and the site of carboxylation in the chloroplast, was reported to be higher in plants grown at low light intensities (Holmgren, 1968, Crookston et al, 1975.…”
Section: Net Co 2 Assimilation Ratementioning
confidence: 99%